Pengaruh Variasi Konsentrasi Hidroxy Propyl Methyl Cellulose (HPMC) terhadap Stabilitas Fisik Gel Ekstrak Tembakau (Nicotiana tabaccum L.) dan Aktivitasnya terhadap Streptococcus mutans - Yati, Kori; Jufri, Mahdi; Gozan, Misri; Mardiastuti, Mardiastuti; Dwita, Lusi Putri (UI Scholars Hub, 2018)
Tobacco extract had been proven to have antimicrobial activity against Streptococcus mutans. To maximize the use of tobacco extract on topical use as an antibacterial, it could be formulated into a pharmaceutical preparation. This study aimed to formulate tobacco extract in gel preparation by using Hidroxy Propyl Methyl Cellulose (HPMC) as a gelling agent and to test its activity on S. mutans. The tobacco extract gel was prepared in 3 formulas with variations of HPMC concentration of 1.5% (F1), 2% (F2) and 2.5% (F3). The research began with tobacco extraction, then continued with characteristics evaluation. The extract was formulated in gel form and evaluated for 12 weeks of physical stability. Antibacterial activity was tested using the diffusion method. The evaluation results of tobacco extract gel showed that all formulas were stable during 12 weeks storage. Antimicrobial activity against S.mutans showed inhibitory diameter of F1, F2 and F3, were 9,07 mm, 19,53 mm, and 11,57 mm respectively. The test was continued by determining the relative potential of F2 compared to erythromycin. The test results showed 1.2 x 10-2 relative potential compare to erythromycin. Based on the results of this study, it can be concluded that HPMC concentration difference did not give significant difference to the physical stability of tobacco gel, with the best antibacterial activity on S. mutans obtained from F2.